2020
DOI: 10.1080/23311975.2020.1823580
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationships of work-related factors, person-environment fit, and employee turnover intention

Abstract: Retaining human resources is essential for a company's competitiveness. Losing a high-capacity employee can hurt a company's performance. In this study, we investigate the inter-relationship among work-related factors, for instance, job stress, person-environment-fit, and quitting intention of employees in Thailand. Data were collected from 400 office workers in Bangkok, Thailand, utilizing structured questionnaires derived from the conceptual framework. The gathered data were analyzed using the structural equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 20 publications
12
26
1
1
Order By: Relevance
“…Joarder proved that the work environment or working conditions have a negative and significant influence on turnover intention. Ketkaew et al, (2020) prove that the work environment hurts turnover intention. Based on the theoretical basis and various research results, the following hypotheses can be put forward.…”
Section: Theoretical Conceptmentioning
confidence: 94%
“…Joarder proved that the work environment or working conditions have a negative and significant influence on turnover intention. Ketkaew et al, (2020) prove that the work environment hurts turnover intention. Based on the theoretical basis and various research results, the following hypotheses can be put forward.…”
Section: Theoretical Conceptmentioning
confidence: 94%
“…Internal organizational or leadership behavior-related factors refer to organizational training, compensation systems, organizational culture, internal service quality, leadership behavior, and other variables that affect turnover intention [31][32][33]. For example, Zhang researched private companies' managers to explore the reasons for the sales managers turnover in private companies in Guangdong and revealed that the main reasons were job compensation and the companies' development prospects [34].…”
Section: Factors Influencing Employee Turnover Intentionmentioning
confidence: 99%
“…Tujuan akhirnya adalah untuk menghindari penurunan kinerja karyawan karena PT. JNE Cabang Kota Malang bergerak dibidang jasa (Ketkaew et al, 2020;Juvendy & Hendriati, 2020). Menariknya adalah pemberian kompensasi terhadap karyawan perlu mempertimbangkan regulasi perusahaan seperti, sistem perusahaan untuk penggajian karyawan, kebijakan kompensasi perusahaan lainnya yang didasarkan atas prestasi kerja dengan syarat-syarat yang berlaku (Baker et al, 1988;Nzyoka & Orwa, 2016).…”
Section: Pendahuluanunclassified